The Aesthetics of Effacement: A comparative study of the Literary Output of Nikolai Gogal and Oscar Wilde - MCCONE, BRIGIT KATHARINE (Trinity College Dublin. School of Lang, Lit. & Cultural Studies. Discipline of Russian, 2019)
This thesis is the first comprehensive comparative study of the 19th-century RussoUkrainian satirist Nikolai Gogol and the 19th-century Anglo-Irish satirist Oscar Wilde, presenting a survey of their thematic and stylistic parallels within a potentially explanatory framework of their shared imperatives as sexually and ethnically closeted authors. Part One conducts a detailed thematic survey of both authors' conception of the artistic process as expressed in their fiction, examining whether parallels could be indicative of shared exposure anxiety, before concluding with a review of the dominant stylistic features of each author's fiction as products of a shared imperative toward the generation of interpretative suspense and the facilitation of plausibly deniable self-expression. A range of genre theorists are invoked to diagnose genres defined by interpretative suspense, while theories of literary negativity hitherto applied to Nikolai Gogol are applied to Oscar Wilde. Part Two opens with a review of evidence for the diagnosis of each author's sexuality and ethnicity as well as the extent to which they may be claimed to be closeted, utilizing postcolonial and queer theory while seeking their intersection. The remaining five chapters are a detailed thematic analysis of parallels in the depiction of sexuality, ethnicity and identity in the work of both authors, utilizing the Jungian individuation cycle as a potentially explanatory model of the imagination's response to repression. This thesis contributes to scholarship by offering a new aesthetic framework for the evaluation of Oscar Wilde, through the application of theories of literary negativity previously applied to Nikolai Gogol, as well as toward the contextualization of Nikolai Gogol as a closeted writer, while pointing the way for further comparative study of Anglo-Irish and Russo-Ukrainian literature. It also examines whether the poetic cycle of Wilde's Poems could be used as the basis of an improved Jungian model of the homoerotic male imagination.
APPROVED
Keywords: Oscar Wilde; Nikolai Gogol; Closeting; Jungian literary criticism; Queer theory; Postcolonial theory; Genre theory